Aproximación histórica a la figura del sofista - Sánchez Manzano, María Asunción; Rus Rufino, Salvador (1990)
'Sophistés' was any man possissing masterful habilities in early V Century; so the epic poets and the ancient Ionian philosophers were thus 'sophistaí'. This paper offers an explanation of the different uses of the word 'sophistés' during this Century, when a new pedagogical and philosophical doctrine appears, and the meaning of this word changes (mainly Plato, Aristoteles and Isocrates' works).
Keywords: Sofistas; Filosofía; Lengua latina